Penyelesaian Pemutusan Hubungan Kerja Terhadap Pekerja PT Tirta Investama (Aqua) Solok - Maudyta Putri Oktyawati; Khairani Khairani; Darnis Darnis (Lareh Law Review, 2023)
Abstract Unilateral termination of employment by PT Tirta Investama (Aqua) Solok was the result of a strike by workers demanding unpaid overtime wages from 2016 to 2022. Government involvement, in the form of monitoring and supervising the termination of employment and the fulfillment of workers' rights by companies, particularly by the local Manpower Office, is necessary. The issues addressed in this research are: 1) The mechanism of employment termination carried out by PT Tirta Investama (Aqua) Solok; 2) The fulfillment of the rights of workers affected by the employment termination by PT Tirta Investama (Aqua) Solok; and 3) The actions taken by the Solok District Manpower Office in response to the employment termination by PT Tirta Investama (Aqua) Solok. To address these issues, a normative empirical research method is used, which involves examining the implementation of regulations and how they are applied in society. Both primary and secondary data are used, collected through interviews and document studies. Based on the research results, the following conclusions can be drawn: 1) The mechanism of employment termination by PT Tirta Investama (Aqua) Solok is considered unilateral and not in accordance with the reasons stated in Article 153 and Article 154A of the Manpower Law, as updated by the Job Creation Law; 2) The company has provided severance pay and compensation to the workers affected by the employment termination, but the amounts are not appropriate for the workers; and 3) The Solok District Investment and Integrated One-Stop Service and Manpower Office has attempted to resolve the dispute by summoning both parties before mediation and holding several meetings with the management of PT Tirta Investama (Aqua) Solok to advocate for the rights of terminated workers in a mutually beneficial manner.